Pengaruh Self Efficacy terhadap Kinerja Pegawai pada Sekretariat Komisi Pemilihan Umum Daerah (Kpud) Kabupaten Luwu Timur - Khaerana, Khaerana (Jurnal Ecoment Global, 2020)
This research was conducted to determine the effect of self-efficacy on employee performance at the Secretariat of the Regional General Election Commission (RGEC) of East Luwu Regency. This research is quantitative descriptive with data collection methods through observation, interviews, questionnaires and documentation. The number of respondents in this research were 28 employees. The tools of data analysis in this research is a simple linear regression analysis using SPSS version 20. From the results of the t test analysis shows the value of t count (4,233) Â > t table (1,706) Â and the significance value of 0,000 < 0.05, so it can be concluded that Self Efficacy has a positive and significant effect on performance employee at the Secretariat of Regional General Election Commission (RGEC) of East Luwu Regency. The higher of self efficacy that is owned by an employee, then the more performance will increase.Keywords: Self Efficacy, Employee Performance